Feature Selection of Motor Activity in Intervals of Time with Genetics Algorithms for Depression Detection - Espino-Salinas, Carlos H.; Galván-Tejada, Carlos E.; Sánchez-Reyna , Ana G.; Luna-García, Huizilopoztli; Gamboa-Rosales, Hamurabi; Morgan-Benita, Jorge A.; Celaya-Padilla, José M.; Galván-Tejada, Jorge I. (Revista Mexicana de Ingenieria Biomedica, 2023)
It is estimated that depression affects more than 300 million people in worldwide. Unfortunately, the current method of psychiatric evaluation requires a great effort on the part of clinicians to collect complete information. The aim of this paper is determine the optimal time intervals to detect depression using genetic algorithms and machine learning techniques; from motor activity readings of 55 participants during a week at one-minute intervals. The time intervals with the best performance in detecting depression in individuals were selected by applying Genetic Algorithms (GA). Methodology. 385 observations of the study participants were evaluated, obtaining an accuracy of 83.0 % with Logistic Regression (LR). Conclusion. There is a relationship between motor activity and people with depression since it is possible to detect it using machine learning techniques. However, the changes in the variables of the time intervals could be established as key factors since, at different times, they could give good or bad results because the motor activity in the patients could vary. However, the results present a first approximation for developing tools that help the opportune and objective diagnosis of depression.